Post-Pandemic Transformation of Zakat, Infaq, and Sadaqah (ZIS): Implications for Social Welfare and Economic Recovery - M Zaky Mubarak Lubis; Gusti Dirga Alfakhry Putra; Hidayatul Husna; Mansha Rafiq (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2026)
This study examines how the collection and distribution of Zakat, Infaq, and Sadaqah (ZIS) transformed during the COVID-19 pandemic. It provides forecasts for 2024, with a particular focus on their implications for social welfare and economic recovery in the post-pandemic era. The study utilized secondary data obtained from BAZNAS monthly reports covering January 2020 to December 2023, a period that captures the initial peak of the COVID-19 crisis and the subsequent recovery phase. Due to the non-normal distribution of the data, the Wilcoxon signed-rank test was employed to assess differences in ZIS collection and distribution between the peak and recovery periods. Additionally, Seasonal Autoregressive Integrated Moving Average (SARIMA) models were applied to forecast future trends. The findings revealed statistically significant differences between the peak and recovery periods in both ZIS collection and distribution, indicating a structural shift in philanthropic behavior and institutional responsiveness after the pandemic. The SARIMA results demonstrated strong capability in capturing seasonal patterns and long-term trends, particularly the pronounced increase in ZIS activities during Ramadan. While the SARIMA model provided a robust foundation for understanding seasonal dynamics and short-term trends, incorporating additional data or hybrid forecasting approaches may enhance predictive accuracy.